Prawn farming: an attractive prospect - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Africa has certain advantages that could be exploited to make prawn farming competitive on a world market at present dominated by Asia and South America. It is an attractive prospect. Prawn farming remains under developed. Only 1.7 million tonnes...